D-LEARN: A digital game for Software Architecture education - Caminha, Luis Otávio Lima; Marques, Anna Beatriz (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: Educational games have been increasingly used to make learning fun, interactive, and less massive for the students. This approach is called game-based learning. In Information Systems education, several games can be found to help students better understand real-world situations, the impact of their decisions, and teamwork through a simulated environment. From this perspective, games such as LEARN Board Game, a non-digital game that aims to help teach software architecture through a board and card game, are essential in software architecture professors’ tools to solve abstract problems. Problem: LEARN has limitations because it is a non-digital game. For example, we can mention the non-ecological way the game is made (using paper and plastic) and the difficulties of making simple changes, such as changing the text of a card. Solution: Even though it is a tool that helps teachers, its handling could be more satisfactory for those who use it. Thus, this work aimed to build a digital version of LEARN, called D-LEARN, improving its negative points and maximizing its positive points. IS Theory: This research was developed under the aegis of Design Theory, explicitly seeking to adopt a more practical vision, using visual elements through design components to assist learning and teaching. Method: The research and development methodology was the Design Science Research (DSR), which proposes cycles of activities for building or updating an artifact that aims to solve a real-world problem with a pragmatic and satisfactory approach. Results: The digital game obtained an excellent quality score according to the MEEGA+ questionnaire evaluation, surpassing the quality score of the non-digital game. Contributions: The main contribution is to enable a game that assists in teaching software architecture, promoting more significant learning and satisfaction for students.